Physiological profile of CAX1a TILLING mutants of Brassica rapa exposed to different calcium doses - Navarro-León, Eloy; Ruiz, Juan Manuel; Graham, Neil; Blasco, Begoña (Elsevier, 2018)
Calcium (Ca) is an essential macronutrient for plants and its homeostasis is basic for many processes in plants. Therefore, both Ca deficiency and toxicity constitute potential issues for crops. CAX1 transporter is a potential target to obtain plants with better Ca homeostasis and higher Ca concentration in edible parts. Three Brassica rapa mutants for CAX1 were obtained through TILLING. The objective of this work is to evaluate the growth, physiological state and nutrients concentration of these mutants grown with different Ca doses. The mutants and the parental line were grown under low, control and high Ca doses and parameters related to their oxidative stress, photosynthetic performance and nutrients concentration were determined. BraA.cax1a-4 and BraA.cax1a-7 mutants presented lower total Chl, an altered photosynthesis performance and higher ROS levels. BraA.cax1a-12 mutant grew better under high Ca conditions. All mutants accumulated more Ca and Mg in leaves under control and high Ca doses and accumulated more Fe regardless the Ca dose. The results obtained point to BraA.cax1a-12 as a potential candidate for biofortification with Fe, Ca and Mg since it accumulate higher concentrations of these elements, do not present an altered growth and is able to tolerate higher Ca doses.